Priming effect on word reading and recall - Faria, Isabel Hub (2017)
This study focuses on priming as a function of exposure to bimodal stimuli of European Portuguese screen centred single words and isolated pictures inserted at the screen’s right upper corner, with four kinds of word-picture relation. The eye movements of 18 Portuguese native university students were registered while reading four sets of ten word-picture pairs, and their respective oral recall lists of words or pictures were kept. The results reveal a higher phonological priming effect when recalling words. Results are discussed taking into consideration the eye movements’ behaviour values (number and duration of fixations, and number of transitions between word and picture).